Revisión documental sobre las estrategias pedagógicas para la producción y el fortalecimiento de textos narrativos en estudiantes de básica primaria (2021)
This monograph proposes a documentary review to identify the pedagogical strategies and digital tools used in the school contexts of the last six years, for the production and strengthening of narrative texts in elementary school students. For this, information was collected from national and international degree projects and scientific articles between the years 2015-2021. Through the systematic review, thirty-seven academic sources on the teaching and learning processes of textual production were identified. The monograph was divided into three moments: first, the study units were identified, secondly, the organization of the information was carried out through a bibliographic matrix and the preparation of RAES; third, data processing was carried out through four categories of analysis; textual typologies, compositionstrategies, digital pedagogical tools and language disorders that make it difficult to write narrative texts. Finally, conclusions.